Situation of Brain Drain in Pakistan, with a Focus on the Healthcare Sector (The Pakistan Development Review, 2025)
In this brief, we draw attention to Pakistan with the purpose of diversifying research on brain drain of individuals who migrate from the country primarily in search of a better quality of life and institutions, particularly focusing on the healthcare sector. Brain drain in Pakistan has become a perpetually rising phenomenon with more and more highly skilled workers leaving the country, yet there is relatively less research on this group. Pakistan offers a unique insight into migration of skilled workers from developing states due to the recent economic turmoil, as well as the consequent effects on the country, the repercussions for those who remain behind, and policy instruments used to maximise benefits for all stakeholders. Brain drain in the country has led to a shortage of highly qualified medical professionals, and poor returns on investment by the government.INTRODUCTIONIn discussions about the flow of human capital, there is a common belief that developing countries are increasingly becoming a source of talented individuals who eventually end up in developed countries due to a lack of adequate institutions or environments in their home countries to support them. International migration benefits immigrants by allowing them to achieve a higher income and better quality of life.While origin countries experience an influx of remittances, increased trade and technological transfers, they also incur losses in human capital and subsequent brain drain. Despite increasing trends in brain drain, most studies on migrants’ demographics and sociology tend to neglect it.In this brief, we draw attention to Pakistan as a significant region to add to research and theory on studies of migration patterns in developing countries. Pakistan, we argue, exemplifies the global trend of brain drain as approximately 832,339 Pakistanis went abroad for employment in 2022, which is the highest number since 2016 and the third-highest ever recorded according to the Bureau of Emigration and Overseas Employment (BEOE). Additionally, official records indicate that among those who traveled overseas in 2022, over 92,000 were graduates and more than 350,000 were trained workers and labourers (BEOE, 2022). Therefore, Pakistan -a low income country- presents a distinctive prospect to analyse a rapidly growing and diverse brain drainphenomenon as it offers important insights for migration scholars in comprehending the various factors associated with high-skilled worker migration, its effects on the country, the repercussions for those who remain behind, and policy instruments used to maximise benefits for all stakeholders.